Analysis on the dust prevention mechanism of air curtain in fully mechanized excavation tunnel - Hao Wang; Chuangye Xin; Shouqing Lu; Yongliang Zhang; Zhanyou Sa; Jinxu Tao; Zhuang Liu (International Journal of Coal Science & Technology)
Abstract Aiming at reducing the dust pollution during the tunneling process and improving the application efficiency of air curtain dust prevention technology, according to the changes of radial jet velocity (v r), axial extraction velocity (v e) and extraction distance (L) in the formation process of air curtain, the numerical simulation method was used to analyze the rules of airflow structure evolution and the diffusion characteristics of dust particles in fully mechanized excavation tunnel. The results indicate that as v r and v e increase, the migration path of the wall jet of the air curtain changes into an axial direction; as L decreases, the migration distance increases accordingly. These phenomena make the airflow distribution in the working face tends to be uniform. The dust diffusion distance reduces as well, wherein, the range of the discrete area of dust particles decreases sharply, until all dust particles are concentrated in the accumulation area. On this basis, the v r, v e and L were optimized and applied in the 63up08 fully mechanized working face. By the application of the optimal parameters, the average dust removal efficiency at the driver’s position increased by 71%. The dust concentration was reduced and the working environment had been improved effectively.